Հաճոյախոսությունները միջմշակութային հաղորդակցման համատեքստում - Բրուտյան, Լ. Գ.
В статье анализируются разные типы комплиментов, являющихся одним из видов речевого этикета и выполняющих одновременно важную коммуникативную контактоустанавливающую функцию. Показывается, что при межкультурной коммуникации необходим учёт разнообразных прагма-и-социокультурных факторов, влияющих на адекватное восприятие комплиментов и, как следствие, успешность/неуспешность процесса коммуникации. In the paper, different types of compliments, one of the kinds of speech etiquette which have at the same time an important communicative contact-establishing function, are analysed. It is shown that in the process of intercultural communication it is necessary to take into account various pragma- and sociocultural factors that affect the adequate perception of compliments, hence, the success/failure of the communication process.
Keywords: Լեզվաբանություն